FACTORS INFLUENCING SPEECH DELAY IN EARLY CHILDHOOD: A LITERATURE REVIEW BASED ON VYGOTSKY'S THEORY - Irda Rafika; Salpina (STMIK Indonesia Banda Aceh, 2026)
Language development is an important aspect in the growth and development of early childhood because it is directly related to thinking skills , social interaction , and learning readiness . One of the disorders that often appears during the golden age (0–6 years ) is speech delay , which is a condition when a child is not yet able to use spoken language according to his developmental stage . This article aims to identify and analyze factors that influence speech delay in early childhood based on Vygotsky 's social development theory . The study was conducted using the Systematic Literature Review (SLR) method of national and international scientific articles published between January 2019 and December 2025. Of the 245 articles found through four databases, 25 articles met the inclusion criteria and were analyzed thematically . The results of the study indicate that speech delay is influenced by internal factors of the child ( cognitive and emotional ), family factors ( parenting patterns and verbal stimulation ), educational environmental factors ( the role of teachers and learning methods ), and socio-technological factors ( social interaction and exposure to digital devices ). Based on Vygotsky's theory , social interaction through the Zone of Proximal Development (ZPD) and scaffolding plays a central role in accelerating children's language development .